Influence of working gas properties on MWPC anode wire modulation effect - 王小胡 陈孝强 (Chinese physics C, 2015)
For MWPCs used for X-ray position detection, simulation studies of the anode wire modulation effect of the detector were carried out using the Garfield program. Different gas mixtures were used as the working gas in the simulation, so as to obtain the influence of the X-ray cross section and electron diffusion coefficient of the working gases on the anode wire modulation effect of an MWPC with anode wire spacing of 2 mm. Results show that, though a working gas with higher X-ray cross section implies a larger average drift distance for the ionized electrons, such gas mixtures are of little use in improving the anode wire modulation effect of MWPCs. It is found that the transverse electron diffusion coefficient is the determining factor for the extent of the anode wire modulation effect in the detector.